A dual wavelength-activatable gold nanorod complex for synergistic cancer treatment. Issue 28 (30th June 2015) - Pacardo, Dennis B.; Neupane, Bhanu; Rikard, S. Michaela; Lu, Yue; Mo, Ran; Mishra, Sumeet R.; Tracy, Joseph B.; Wang, Gufeng; Ligler, Frances S.; Gu, Zhen
Abstract : A multifunctional gold nanorod complex was formulated for synergistic anticancer treatment upon ultraviolet (UV) and infrared (IR) light dual irradiations. Abstract : A multifunctional gold nanorod (AuNR) complex is described with potential utility for theranostic anticancer treatment. The AuNR was functionalized with cyclodextrin for encapsulation of doxorubicin, with folic acid for targeting, and with a photo-responsive dextran-azo compound for intracellular controlled drug release. The interaction of a AuNR complex with HeLa cells was facilitated via a folic acid targeting ligand as displayed in the dark-field images of cells. Enhanced anticancer efficacy was demonstrated through the synergistic combination of promoted drug release upon ultraviolet (UV) light irradiation and photothermal therapy upon infrared (IR) irradiation. This multifunctional AuNR-based system represents a novel theranostic strategy for spatiotemporal delivery of anticancer therapeutics.